Myocarditis in Children: Clinical Overview, Diagnosis and Treatment - Larisa A. Balykova; Anna V. Krasnopolskaya; Ekaterina A. Vlasova (Педиатрическая фармакология)
The lecture presents modern views on the problem of myocarditis in pediatrics. Current ideas about the definition, prevalence, etiology and pathogenesis of inflammatory myocardial lesions in children are presented. Features of clinical manifestations of the disease in patients of different age groups, difficulties of diagnosis and treatment of myocarditis and its complications are disclosed in accordance with federal clinical recommendations. Special attention is paid to diagnostic approaches adjusted with the European society of cardiologists, including first and second level techniques, determination of indications for their implementation and diagnostic capabilities, as well as differential diagnosis of myocarditis with other cardiological diseases. Issues of heart failure treatment in myocarditis and indications for heart transplantation for patients under 18 years of age were also discussed. The lecture has illustrated clinical examples that clearly demonstrate the diversity of the clinical picture and the ambiguity of myocarditis prognosis in children and teenagers.